How can manufacturing companies improve production planning resilience against supply chain disruptions - Holopainen, Pihla (My University, 2025)
Recent disruptions in supply chains (pandemic, geopolitical and logistical) have raised the need to focus on the resilience of production planning in the manufacturing industry. The purpose of this literature review is to examine how manufacturing companies can strengthen the resilience of production planning. A systematic literature review was conducted using several databases covering the years 2020–2025. The criteria for the search were: peer-reviewed, English- language, manufacturing industry and self-performed data extraction and selection of articles. The most common disruptions were observed to be fluctuations in demand and production caused by the pandemic and logistical disruptions, such as the Suez Canal Blockage. The disruptions were visible in upstream supply, downstream demand and internal processes. The most important tools for resilient production planning were found to be production speed adjustment (inventory and cost control), multi-skilled workforce and redundancy (safety stocks and capacity buffers). The best results came from combining strategies and with proactive, systematic disruption management. Digitalisation (digital twin, CPPS/IoT, analytics and artificial intelligence) improved visibility, collaboration and responsiveness, supporting the development of resilient production planning. The results provide a concrete framework for companies to develop and prioritize flexibility investments and reinforce disruption resilience in production planning. The results were limited by the time frame of 2020–2025, the use of English and variations in terminology (resilience, flexibility, agility).

Viimeaikaiset toimitusketjujen häiriöt (pandemia, geopoliittiset ja logistiset) ovat korostaneet tarvetta keskittyä valmistavan teollisuuden tuotannonsuunnittelun joustavuuteen. Tämän kirjallisuuskatsauksen tarkoituksena on tarkastella, miten valmistavan teollisuuden yritykset voivat vahvistaa tuotannonsuunnittelun häiriönsietokykyä. Tutkimus toteutettiin systemaattisena kirjallisuuskatsauksena, jossa hyödynnettiin useita tietokantoja vuosilta 2020– 2025. Hakukriteereinä käytettiin vertaisarvioituja englanninkielisiä artikkeleita, jotka käsittelevät valmistavaa teollisuutta. Yleisimmiksi häiriöiksi tunnistettiin pandemian aiheuttamat kysynnän ja tuotannon vaihtelut, sekä logistiset häiriöt, kuten Suezin kanavan tukkeutuminen. Häiriöt näkyivät toimitusketjun alkupäässä, loppupäässä ja yritysten sisäisissä prosesseissa. Tärkeimmiksi tuotannonsuunnittelun resilienssiä vahvistaviksi työkaluiksi todettiin tuotantonopeuden säätö (varastojen ja kustannusten hallinta), monitaitoinen henkilöstö ja redundanssi (varmuusvarastot ja kapasiteettipuskurit). Parhaat tulokset saavutettiin yhdistämällä strategioita sekä ennakoivalla, järjestelmällisellä häiriöiden hallinnalla. Digitalisaatio (digitaalinen kaksonen, CPPS/IoT, analytiikka ja tekoäly) paransi näkyvyyttä, yhteistyötä ja reagointikykyä, mikä tuki joustavan tuotannonsuunnittelun kehittämistä. Tutkimuksen tulokset tarjoavat yrityksille konkreettisen viitekehyksen seurattavaksi, jonka avulla yritykset voivat kehittää ja priorisoida investointeja joustavuuteen sekä vahvistaa tuotannonsuunnittelun häiriönsietokykyä. Tuloksia rajoittavat aikaväliltä 2020–2025 valikoidut lähteet, englanninkielisten lähteiden käyttö ja terminologian vaihtelut (resilienssi, joustavuus, ketteryys).
Keywords: production planning; manufacturing industry; resilience; flexibility; digitalisation; manufacturing industry; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; fi=Tuotantotalouden ja tietojärjestelmätieteen kandidaattiohjelma|en=Bachelor’s Programme in Industrial Management and Information Systems|